2015
DOI: 10.1038/ejhg.2015.211
|View full text |Cite
|
Sign up to set email alerts
|

A de novo microdeletion of SEMA5A in a boy with autism spectrum disorder and intellectual disability

Abstract: ,4,5,11,15 Semaphorins are a large family of secreted and membrane-associated proteins necessary for wiring of the brain. Semaphorin 5A (SEMA5A) acts as a bifunctional guidance cue, exerting both attractive and inhibitory effects on developing axons. Previous studies have suggested that SEMA5A could be a susceptibility gene for autism spectrum disorders (ASDs). We first identified a de novo translocation t(5;22)(p15.3;q11.21) in a patient with ASD and intellectual disability (ID). At the translocation break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 35 publications
2
42
0
Order By: Relevance
“…In addition to PLXNA2 , mutations in SEMA5A ( Mosca-Boidron et al, 2016 ; Weiss et al, 2009 ), RAP1 ( Stornetta and Zhu, 2011 ), and CXCL12/CXCR4 ( Toritsuka et al, 2013 ) associate with increased risk for neuropsychiatric illness. Of interest, the scaffold protein Shank3 negatively regulates integrin-mediated cell adhesion by binding Rap1 and, thereby, sequestering it away from the plasma membrane ( Lilja et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to PLXNA2 , mutations in SEMA5A ( Mosca-Boidron et al, 2016 ; Weiss et al, 2009 ), RAP1 ( Stornetta and Zhu, 2011 ), and CXCL12/CXCR4 ( Toritsuka et al, 2013 ) associate with increased risk for neuropsychiatric illness. Of interest, the scaffold protein Shank3 negatively regulates integrin-mediated cell adhesion by binding Rap1 and, thereby, sequestering it away from the plasma membrane ( Lilja et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…During mouse postnatal development, Sema3F regulates excitatory synapse formation in apical dendrites of layer V pyramidal neurons, and loss of this signaling increases apical dendrite spine density and the excitability of these neurons (Demyanenko et al, 2014;Tran et al, 2009). In humans, semaphorin and plexin gene variants are associated with a number of neurodevelopmental disorders, including autism spectrum disorder (Cheng et al, 2013;Fujii et al, 2011;Kim et al, 2017;Mosca-Boidron et al, 2016;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years three family based GWAS had identified potential autism susceptibility variants at SEMA5A (rs10513025), MACROD2 (rs4141463) and MSNP1 (rs4307059), all expressed in brain. SEMA5A is an intriguing candidate gene for autism: a de novo microdeletion was reported in this gene in a patient with ASD and ID [Mosca‐Boidron et al, ], and it has been shown to regulate synaptogenesis in hippocampus [Duan et al, ]. The associated variant was suggested to have an impact on the expression of the SEMA5A gene, which was found downregulated in brains and lymphoblastoid cell lines of patients with ASD [Cheng, Quinn, & Weiss, ; Melin et al, ; Weiss et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…All ASD patients met ICD‐10 or DSM‐IV TR criteria for autism, Asperger disorder or pervasive developmental disorder not otherwise specified (PDD‐NOS), assessed using ADI‐R (Autism‐Diagnostic Interview‐Revised) [Lord, Rutter, & Le Couteur, ] and when possible also ADOS (Autism Diagnostic Observation Schedule) [Lord et al, ]. Additional information about case and control samples for each country regarding recruitment, diagnostic approach and selection can be found in previous publications [Bacchelli et al, ; Mosca‐Boidron et al, ; Prandini et al, ; Toma et al, ; Torrico et al, ; van Steijn et al, ; Waltes et al, ]. In this study, ASD patients were considered high functioning if their IQ score was greater than 70.…”
Section: Methodsmentioning
confidence: 99%